2014
DOI: 10.1007/s40211-014-0124-8
|View full text |Cite|
|
Sign up to set email alerts
|

Das Zusammenwirken von Rhodiola rosea (Eisenwurz) und Antidepressiva

Abstract: Prescribing Rhodiola rosea with paroxetine, pharmacokinetic and -dynamic interactions have to be assumed. The symptoms of the patient can be interpreted as a serotonergic syndrome. Because of its different effects, the plant is widely used. An increase of clinical relevant risks should be considered in the add-on treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Rhodiola can modulate hypothalamic-pituitary-adrenal (HPA) axis activity as well as that of several neurotransmitters [ 104 ]. Maniscalco et al recently reported the case of a 68-year-old female patient with recurrent moderate depressive disorder with somatic syndrome who developed vegetative syndrome, feelings of restlessness, and trembling since she began ingesting Rhodiola supplements in addition to paroxetine [ 107 ]. These symptoms may have been due to serotonergic syndrome [ 107 ]; therefore, it is possible that concomitant use of Rhodiola and selective SSRIs may lead to an excess of serotonin in the CNS and/or in peripheral nervous system with subsequent increased clinical risks.…”
Section: Interaction Between Weight-loss-related Herbal Products Amentioning
confidence: 99%
“…Rhodiola can modulate hypothalamic-pituitary-adrenal (HPA) axis activity as well as that of several neurotransmitters [ 104 ]. Maniscalco et al recently reported the case of a 68-year-old female patient with recurrent moderate depressive disorder with somatic syndrome who developed vegetative syndrome, feelings of restlessness, and trembling since she began ingesting Rhodiola supplements in addition to paroxetine [ 107 ]. These symptoms may have been due to serotonergic syndrome [ 107 ]; therefore, it is possible that concomitant use of Rhodiola and selective SSRIs may lead to an excess of serotonin in the CNS and/or in peripheral nervous system with subsequent increased clinical risks.…”
Section: Interaction Between Weight-loss-related Herbal Products Amentioning
confidence: 99%
“…In HDI case reports, some drug classes are over-represented. These classes include immunosuppressants [18,[34][35][36][37], anticancer drugs (ATC class L01, three cases, CR 4, 5, 10) [19,38,39]. This observation confirms that most cases are related to long-term conventional treatments and small therapeutic index drugs.…”
Section: Case Reportsmentioning
confidence: 55%
“…Among these cases, 12 mention CYP isoenzymes (CYP2C9, CYP1A2, CYP2D6, CYP3A4, CYP3A5). In only one case (CR 17), a pharmacodynamic interaction is mentioned with the addition of serotonin syndrome [37].…”
Section: Case Reportsmentioning
confidence: 99%
“…One clinical case reported a young healthy woman who had a significant tachyarrhythmia whilst taking a combination of escitalopram and Rhodiola (McGovern & McDonnell, 2010). Moreover, one other clinical case reported a 68‐year‐old female patient, with recurrent moderate depressive disorder with somatic syndrome, who developed vegetative syndrome, restlessness feeling and trembling, since she began to ingest Rhodiola in addition to paroxetine (Maniscalco et al, 2015). Therefore, the risk of pharmacokinetic and pharmacodynamic interactions of this species with SSRIs must be assumed.…”
Section: Herb Interactions With Drugs Acting On the Cns And Pnsmentioning
confidence: 99%